Resistance Mechanisms, Epidemiology, and Approaches to Screening for Vancomycin-Resistant Enterococcus in the Health Care Setting - Faron, Matthew L. (J Clin Microbiol, 2016)
Infections attributable to vancomycin-resistant Enterococcus (VRE) strains have become increasingly prevalent over the past decade. Prompt identification of colonized patients combined with effective multifaceted infection control practices can reduce the transmission of VRE and aid in the prevention of hospital-acquired infections (HAIs). Increasingly, the clinical microbiology laboratory is being asked to support infection control efforts through the early identification of potential patient or environmental reservoirs. This review discusses the factors that contribute to the rise of VRE as an important health care-associated pathogen, the utility of laboratory screening and various infection control strategies, and the available laboratory methods to identify VRE in clinical specimens.